2008
DOI: 10.1007/s12035-008-8027-y
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase C Mediated Modulation of TRPV1 Channels

Abstract: The Transient Receptor Potential Vanilloid type 1 (TRPV1) channels are involved in both thermosensation and nociception. They are activated by heat, protons and capsaicin, and modulated by a plethora of other agents. This review will focus on the consequences of phospholipase C (PLC) activation, with special emphasis on the effects of phosphatidylinositol 4,5-bisphosphate (PIP 2 ) on these channels. Two opposing effects of PIP 2 have been reported on TRPV1. PIP 2 has been proposed to inhibit TRPV1, and relief … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
72
0
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(78 citation statements)
references
References 95 publications
5
72
0
1
Order By: Relevance
“…Among the TRP channels that have been shown to be activated/modulated by PIP 2 are several TRPMs [12,20], TRPC6 [10], TRPV5 [11]. TRPV1, one of the best characterized members of the superfamily, has been shown to be both activated and inactivated by PIP 2 , depending on the experimental conditions [19]. Finally, Saleh [21] have shown a complex mechanism of activation of TRPC1 channels by PIP 2 and PIP 3 , the product of the PI3K-mediated phosphorilation of PIP 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Among the TRP channels that have been shown to be activated/modulated by PIP 2 are several TRPMs [12,20], TRPC6 [10], TRPV5 [11]. TRPV1, one of the best characterized members of the superfamily, has been shown to be both activated and inactivated by PIP 2 , depending on the experimental conditions [19]. Finally, Saleh [21] have shown a complex mechanism of activation of TRPC1 channels by PIP 2 and PIP 3 , the product of the PI3K-mediated phosphorilation of PIP 2 .…”
Section: Discussionmentioning
confidence: 99%
“…**TrpV1 channels also called vanilloid receptors that respond to heat and capsaicin (224) are strongly sensitized by bradykinin and other PLC activators, and it was suggested that PtdIns(4,5)P 2 breakdown relieves a tonic inhibition of these channels by PtdIns(4,5)P 2 (257). However, the lipid regulation of these channels appears to be more complicated as they need phosphoinositides for their activity, and the effects of PtdIns(4,5)P 2 also depend on the extent of stimulation by capsaicin (951,1286,1587) or association with other proteins (728,780) and PtdIns4P may also support their activities (559, 951).…”
Section: Exocytosismentioning
confidence: 99%
“…Indeed, bradykinin [183,184], ATP [185], lipoxygenase products [182,183], prostaglandins [186,187], histamine [188], various neurotrophins (NGF, neurotrophin-3 and -4) [91,102,184], TNF- [189,190], pro-inflammatory chemokines [191], and PAR2 [192,193] were all reported to sensitize TRPV1 via various signal transduction pathways. TRPV1 was shown to be modulated by the protein kinase C (PKC) [183,[194][195][196], phospholipase C (PLC), and phosphatidylinositol 4,5-bisphosphate (PIP 2 ) [184,[197][198][199][200] systems as well as by intracellular ATP [201]. The sensitization process eventually results in the shift of the activation temperature and voltage threshold towards more physiological ranges [195,[202][203][204].…”
Section: Activation and Sensitization Of Trpv1mentioning
confidence: 99%